THE EFFECTIVENESS OF USING HANGMAN GAME TO STRENGTHEN YOUNG LEARNERS’ VOCABULARY - Munikasari, Munikasari; Sudarsono, Sudarsono; Riyanti, Dwi (Journal of English Education Program, 2021)
This research was conducted to find out the evidence of Hangman game in strengthening young learners vocabulary to the Year-7 students of SMP Negeri 4 Teluk Keramat-Sambas in Academic Year 2019/2020. This research was a pre-experimental research with one group pre-test and post-test design. The population of this research was all of Year-7 students with the total number of students were 114 students. The cluster random sampling was taken in this research as the technique of sampling, the participants consisted of 26 students. Referring to the research findings, it revealed that the technique could make students vocabulary increased significantly. It can be seen when the students learn vocabulary. Their attention and involvement indicated that the technique gave positive effect on students vocabulary mastery. They already understood the meaning and how to spell words correctly through Hangman game. The result of the research showed that Hangman game was effective to increase students vocabulary achievement. It was proven by the result of t-test computation is higher than t-critical value (9.24>2.060). This means that the Null Hypothesis (H0) which is the implementation of Hangman game does not affect the young learners vocabulary significantly was rejected, while the Alternative Hypothesis which is the implementation of Hangman game affect the young learners vocabulary significantly was accepted. The score of effect size was 1.8 and qualified as strong effect. To conclude, Hangman game enabled the students to recollect vocabulary easily and generate the students motivation in learning process. Thus, the writer suggested this technique to be implemented in teaching vocabulary.